Virgin Coconut Oil and Extra Virgin Olive Oil on Total Cholesterol and Triglyceride Levels in Hyperglycemic Obese White Rats - Hakim, Dwi Ashariyanti; Bamahry, Aryanti R.; Namirah, Hanna Aulia; Royani, Ida; Syamsu, Rachmat Faisal (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The increasing prevalence of obesity and metabolic disorders highlights the need for effective dietary interventions to improve lipid profiles and reduce cardiovascular risk. This study compares the effects of Virgin Coconut Oil (VCO) and Extra Virgin Olive Oil (EVOO) on lipid profiles, specifically total cholesterol and triglyceride levels, in hyperglycemic obese Wistar rats. Obesity and hyperglycemia are major risk factors for cardiovascular diseases and type 2 diabetes. A total of 24 male rats were divided into three groups: a negative control, a VCO group, and an EVOO group. Rats were placed on a high-fat diet for 14 days and administered 2 mL/kg body weight of either VCO or EVOO via oral gavage. Blood samples were collected at baseline, Day 7, and Day 14 for lipid profile analysis. Results revealed that both VCO and EVOO significantly reduced total cholesterol and triglyceride levels compared to the control group. Notably, EVOO resulted in a more substantial reduction in both total cholesterol (to 130,83 ± 24,807 mg/dL) and triglycerides (to 108,17 ± 17,612 mg/dL) by Day 14, surpassing the effects of VCO. These findings suggest that both oils are effective in improving lipid profiles in hyperglycemic obese rats, with EVOO demonstrating superior efficacy. This study provides valuable insights into the potential of VCO and EVOO as dietary interventions for managing obesity-related metabolic disorders, emphasizing EVOO’s greater effectiveness in lipid management.